APPLICATION OF ANIMATED VIDEOS TO IMPROVE LEARNING OUTCOMES OF PANCASILA EDUCATION IN GRADE V - Alya Azhara (CV Grasta Glory, 2026)
This research aims to determine whether animation video media can improve Pancasila Education learning outcomes for fifth-grade elementary school students. The research was conducted at SD Negeri H. Wukirsari. The type of research used is Classroom Action Research (CAR) , with the subjects being 20 fifth-grade students consisting of 8 males and 12 females. The medium used is animation video media. Data collection techniques include Observation, Interview, Test, and Documentation1. Data analysis uses a mixed method approach. The research was conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The results showed a significant improvement in Pancasila Education learning outcomes. In cycle I, student learning completeness increased from 45% (pre-test) to 55% (post-test). In cycle II, completeness reached 80%. Based on these results, it can be concluded that animation video learning media can improve Pancasila Education learning outcomes for fifth-grade students at SD Negeri H. Wukirsari.